1992
DOI: 10.1104/pp.98.1.399
|View full text |Cite
|
Sign up to set email alerts
|

Mannosyl- and Xylosyl-Containing Glycans Promote Tomato (Lycopersicon esculentum Mill.) Fruit Ripening

Abstract: MATERIALS AND METHODSThe oligosacchadde glycans mannosylal-6(mannosylal-3)mannosyla1-6(mannosyla1-3)mannosyl 1-4-N-acetylglucosamine and mannosylal-6(mannosylal-3)(xylosyl81-2)mannosyl#1-4-N-acetylglucosaminyl(fucosyla1-3)N-acetylglucosamine were infiltrated into mature green tomato fruit (Lycopersicon esculentum Mill., cv Rutgers). Coinfiltration of 1 nanogram per gram fresh weight of the glycans with 40 micrograms per gram fresh weight galactose, a level of galactose insufficient to promote ripening, stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 11 publications
(13 reference statements)
2
45
0
Order By: Relevance
“…Although α-Man and β-Hex are induced by ethylene (Figs. 1H and 2H), they may also further act by promoting ethylene biosynthesis, possibly through free N-glycans, which when injected in the fruit demonstrated ethylene production (14). Altogether, our results provide evidence that α-Man and β-Hex function through degradation of cell wall glycoproteins, followed by an increase in the free N-glycans level.…”
Section: Never Ripe (Nrsupporting
confidence: 66%
See 2 more Smart Citations
“…Although α-Man and β-Hex are induced by ethylene (Figs. 1H and 2H), they may also further act by promoting ethylene biosynthesis, possibly through free N-glycans, which when injected in the fruit demonstrated ethylene production (14). Altogether, our results provide evidence that α-Man and β-Hex function through degradation of cell wall glycoproteins, followed by an increase in the free N-glycans level.…”
Section: Never Ripe (Nrsupporting
confidence: 66%
“…Moreover, blocking of N-glycosylation with tunicamycin delays fruit ripening. Further, when injected in fruits, N-glycans are known to stimulate red coloration and ethylene production (14). To determine the N-glycan processing ability of α-Man and β-Hex, the purified enzymes were incubated with different N-glycans commonly found in fruit pericarp.…”
Section: α-Man and β-Hex Are The Cell Wall Proteins Involved In N-glycanmentioning
confidence: 99%
See 1 more Smart Citation
“…Free N-glycans, which are released from glycoproteins and glycopeptides, occur ubiquitously at micromolar concentrations in various plant cells during the differentiation, growth, and ripening stages, [1][2][3][4][5][6][7][8][9][10] and auxin-like activity has been postulated. 11,12) As a part of a study to elucidate the physiological functions of free N-glycans and the significance of the de-N-glycosylation mechanism working at the differentiating and developing stages of plant cells, Kimura et al analyzed the structural features of free N-glycans occurring in developing seeds, seedlings, and shoots, [5][6][7][8][9] and the functional futures of de-N-glycosylation enzymes, endo--N-acetylglucosaminidase (ENGase) and peptide: N-glycanase (PNGase).…”
mentioning
confidence: 99%
“…9,[13][14][15] They found that two types of free N-glycan, a high-mannose type and the a plant complex type, are always found in developing seeds, hypocotyls undergoing elongation, and ripening fruits. [5][6][7][8][9][10] In such free N-glycans, most high-mannose type structures have a single GlcNAc residue at their reducing end moieties, while plant complex type free N-glycans with xylose/fucose residues have an Nacetylchitobiosyl unit, indicating that the former structures are produced by ENGase and the latter structures by PNGase. It has been found that plant ENGase is highly active against high-mannose type N-glycans bearing the Man 1-2Man 1-3Man 1-4GlcNAc 1-4GlcNAc unit 9,12,13) and that plant PNGase can release high-mannose type, hybrid type, and complex type N-glycans from the peptide backbone.…”
mentioning
confidence: 99%